Tinjauan Hukum Pidana Islam tentang Program Rehabilitasi Anak Pecandu Narkoba di Sumbar - Bintang Putra Awarman (AHKAM, 2026)
The abuse of narcotics among children is a serious problem that threatens social, moral, and legal order, and therefore requires a penal approach that is not only repressive but also oriented toward protection and rehabilitation. This study aimed to examine the implementation of rehabilitation programs for children addicted to narcotics in West Sumatra from the perspective of Islamic criminal law. A normative legal method with a descriptive qualitative approach was employed through an examination of statutory regulations, the principles of Islamic criminal law, and empirical data obtained from the Lembaga Pembinaan Khusus Anak (LPKA) Payakumbuh. The findings show that the rehabilitation of child narcotics abusers is carried out through medical rehabilitation, psychosocial rehabilitation, structured educational and skills development, and religious guidance. From the perspective of Islamic criminal law, narcotics abuse is not categorized as jarimah ḥudūd but can be analogized (qiyās) to khamar because both damage the intellect, so the sanctions imposed fall under ta‘zīr, with an emphasis on educational aspects and behavioral correction. The rehabilitation program implemented is consistent with the objectives of maqāṣid al-syarīʿah, particularly in safeguarding the intellect and life of the child, so that a rehabilitative approach to children addicted to narcotics can be regarded as a form of punishment that is just, humane, and compatible with both national law and Islamic criminal law.